2020
DOI: 10.3390/medicina56110599
|View full text |Cite
|
Sign up to set email alerts
|

Oral Alitretinoin for Patients with Refractory Prurigo

Abstract: Background: prurigo is a chronic skin disorder associated with a history of chronic pruritus. The pathogenesis of prurigo is largely unknown and the treatment of prurigo is unsatisfactory and challenging. Conventional systemic treatments may be beneficial; however, their possible side effects and possible transient efficacy is still a problem. We aimed to present the clinical course and effect of treatment with alitretinoin on patients with prurigo nodularis initially treated with conventional treatments like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recent case reports and case series have found the vitamin A derivative alitretinoin to be an effective treatment for recalcitrant PN, typically at a dosage of 30 mg daily. 12,13 Sustained remission was noted even after discontinuation of the medication. 12 Alitretinoin, which has been demonstrated to be effective in treating dermatitis, 14 was well tolerated.…”
Section: Other New Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent case reports and case series have found the vitamin A derivative alitretinoin to be an effective treatment for recalcitrant PN, typically at a dosage of 30 mg daily. 12,13 Sustained remission was noted even after discontinuation of the medication. 12 Alitretinoin, which has been demonstrated to be effective in treating dermatitis, 14 was well tolerated.…”
Section: Other New Therapiesmentioning
confidence: 99%
“…12,13 Sustained remission was noted even after discontinuation of the medication. 12 Alitretinoin, which has been demonstrated to be effective in treating dermatitis, 14 was well tolerated. Similar to JAK inhibitors, there are minimal data investigating the use of topical retinoids in the treatment of localized PN.…”
Section: Other New Therapiesmentioning
confidence: 99%
“…No meta‐analysis was performed. After this systematic review, some case series suggest that oral alitretinoin alone 64 or in association with methotrexate 65 could be effective, and a pilot study of 10 patients showed that a 12‐week treatment with apremilast was ineffective 66 . Papers with a very high level of evidence were also published (see Therapeutic perspectives).…”
Section: Current Managementmentioning
confidence: 99%